RECIPROCAL TEACHING: APA BERPENGARUH TERHADAP KKM DITINJAU DARI MINAT BELAJAR SISWA - Sansabela, Alda; Rahmi, Depriwana; Yuniati, Suci; Kurniati, Annisah (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
The purpose of this study was to determine whether there were differences in mathematical communication skills in relation to the learning process of implementing Reciprocal Teaching in students who learn through direct learning. The population used in this study consisted only of students of class XI MIA MAN 2 Kampar, where the sample was class XI MIA 1 as the experimental class and XI MIA 2 as the control class. Data collection used tests, observations, questionnaires and documentation. Data were analyzed using TwoWay ANOVA. The results showed that there were variations in mathematical communication skills between students who used the reciprocal learning approach and students who did direct learning: there were differences in this case the mathematical communication skills of students who had high, medium and low learning interests. And there was no interaction between the Reciprocal Teaching learning model and interest in students' mathematical communication skills. So Reciprocal Teaching can be used to influence students' mathematical communication skills.